Digital based e-counseling application on instagram,whatsapp and website to support services counseling at universitas Jambi - Nelyahardi Gutji; Hera Wahyuni; Fellicia Ayu Sekonda; Fitri Fahrianti (Jurnal Konseling dan Pendidikan, 2023)
Counseling services are really needed by students in carrying out their studies. In line with the rapid development of technology, the counseling process can be carried out remotely and with the help of technology connected to the internet network, known as e-counseling. This research aims to develop a product with validity, practicality and effectiveness tests. The research took stages in developing a research design consisting of several stages, namely: 1) preliminary research 2) prototype stage 3) assessment stage. The population of 1291 people, the sample in this study was 350 students taken using purposive sampling techniques. Data collection techniques used include interviews, observation, questionnaires, tests and literature reviews. This indicates that in general, the implementation of the Counseling Application is better than the group that did not use the counseling application in counseling guidance. These test results prove that the Counseling Application is more effective for use by students.